The rising interest in canthoplasty: an analysis of online search trends - Panayi, Adriana C.; Wu, Mengfan; Liu, Qinxin; Haug, Valentin; Yu, Zhen (The journal of craniofacial surgery, 2021)
Canthoplasty as a cosmetic procedure appears to be on the rise in the West. Online search query data offers a powerful tool for analyzing population trends, including changes in patient interest in surgical procedures. Cosmetic surgeons can utilize the internet to increase patient education and interest, as well as to provide information and address misinformation. In this study we sought to verify the increase in cosmetic canthoplasty, for the first time, through analysis of Internet search data, and to establish trends in the interest of Internet users for cosmetic canthoplasty. These trends were subsequently compared with trends in literature publication to establish whether there is a correlation between patient and surgeon interest in the procedure.